2022
DOI: 10.1177/10775595221092961
|View full text |Cite
|
Sign up to set email alerts
|

Statutory Threshold Wording is Associated with Child Maltreatment Reporting

Abstract: The purpose of this study was to determine whether statutory wording of child maltreatment mandated reporting legislation was associated with reporting patterns and substantiation of abuse across U.S. states and territories. Annual state averages for total referrals, referrals screened-out, referrals screened-in, referrals substantiated, and child population (all children in the U.S.; annual average = 74,457,928) were obtained from the 2010-2017 Child Maltreatment Reports. Odds ratios were calculated for: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although I’ve focused here on the tradeoffs between recognition and recall, and on the evidentiary value of disclosures of sexual abuse, similar issues arise in other child maltreatment contexts. Worries about underreporting of child abuse (false negatives) are countered by worries about overreporting (false positives) (Piersiak et al, 2022). Child protection in many jurisdictions veers between highly publicized cases of children dying in abusive homes under the government’s supervision (false negatives) to unnecessary removal of children from falsely accused parents (false positives).…”
Section: Failures To Recognize the Two Types Of Errormentioning
confidence: 99%
“…Although I’ve focused here on the tradeoffs between recognition and recall, and on the evidentiary value of disclosures of sexual abuse, similar issues arise in other child maltreatment contexts. Worries about underreporting of child abuse (false negatives) are countered by worries about overreporting (false positives) (Piersiak et al, 2022). Child protection in many jurisdictions veers between highly publicized cases of children dying in abusive homes under the government’s supervision (false negatives) to unnecessary removal of children from falsely accused parents (false positives).…”
Section: Failures To Recognize the Two Types Of Errormentioning
confidence: 99%
“…Piersiak et al (2022) explored the relationship of the wording of state mandated reporting statutes to rates of reporting and substantiating child maltreatment. They found that states that based mandated reporting on suspicion that maltreatment occurred, rather than a belief it occurred, had higher rates of reporting and screening in for investigation, but lower rates of substantiation.…”
Section: Child Protectionmentioning
confidence: 99%